Pengaruh Model Problem Based Learning Terhadap Literasi Sains Siswa dalam Pembelajaran IPAS Kelas V SDN 26 Cakranegara - Ibad, Muhammad Irsyadul; Husniati, Husniati; Novitasari, Setiani (UNIVERSITAS ISLAM NEGERI MAULANA MALIK IBRAHIM MALANG, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model on students' science literacy in IPAS learning for fifth-grade students at SDN 26 Cakranegara. This research is a quantitative study with a Quasi-Experimental design in the form of a Nonequivalent Control Group Design. The population in this study consists of all fifth-grade students at SDN 26 Cakranegara, comprising three classes: V-A, V-B, and V-C. The research sample consisted of classes V-A and V-B, selected using a random sampling method. Data collection methods included observation and testing. Observation was used to obtain data on the implementation of learning conducted by teachers using the PBL model, while tests were used to collect data on students’ science literacy skills. The data collection instruments were observation sheets for the implementation of PBL and science literacy test sheets. Data analysis techniques used the independent sample t-test. The results of this study indicate that the use of the Problem Based Learning (PBL) model has an effect on the science literacy skills of fifth-grade students in IPAS learning, based on the hypothesis test results which showed a significance value of 0.000, which is less than 0.05. This means that Ho is rejected and Ha is accepted, so it can be concluded that there is an effect of the Problem Based Learning model on students' science literacy in IPAS learning for fifth-grade students at SDN 26 Cakranegara.